DNA barcodes and morphology of P. krempfi, P. mekongensis, and P. elongatus - Yên, Dương Thúy; Kiệt, Nguyễn; Nên, Bùi Sơn; Thường, Nguyễn Văn; Loan, Nguyễn Bạch; Định, Trần Đắc (Vietnam Journal of Biotechnology, 2016)
Three Pangasius species including P. krempfi, P. elongatus and P. mekongensis, are economically important. They can be mis-identified due to similar external appreance at small sizes. This study aimed to distinguish these species based on their differences in DNA barcode, COI (cytochrome c oxidase subunit I) gene, and morphological characteristics. Fish with various sizes (>90 samples/species) were sampled at the lower Mekong delta region. Kimura-2 parameter genetic distances based on COI sequences of three species (15 samples, in which, 4 unique sequences were assigned Genbank accession numbers from KT289877 to KT289880) are relatively high, ranging 9.33 – 12.10 %. Morphological measurements show that coutanble traits including numbers of fin rays and the first gill rakers vary in similar ranges but ratios of metric traits are significantly different among three species (P<0.01). Principle component analysis using metric traits sets three species apart. P. elongatus is characterized by elongated body, long caudal preduncle, large eyes, and retangle palatine tooth plates. P. krempfi differs from P. mekongesis in characteristics on their head. The number of sections, shape and length of barbel are different among three species. Phylogenetic relationship of three species based on morphology and COI sequences indicate that P. krempfi is closer to P. mekongenis rather than P. elongatus, and that the distance between P. mekongenis and P. elongatus is the largest.